2018
DOI: 10.1186/s12885-018-4951-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FGFR gene polymorphisms on response and toxicity of cyclophosphamide-epirubicin-docetaxel-based chemotherapy in breast cancer patients

Abstract: BackgroundThe chemotherapy resistance and toxicity of chemotherapy are major problems in breast cancer treatment. However, candidate biomarkers for predicting clinical outcomes and better prognosis remain lacking.MethodsIn this study, we analyzed possible impact of 8 genetic variants of fibroblast growth factor receptor1–4 (FGFR1–4) on the treatment response and toxicities in 211 breast cancer patients. DNA was extracted from peripheral blood cells, and the genotypes were examined using the TaqMan Pre-Designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 55 publications
1
10
0
1
Order By: Relevance
“…Moreover, both the SNPs revealed the same trend on the UCC, indicating the homogeneous effects of FGFR4 SNPs on the progression and prognosis of UCC. In previous studies, the SNP rs2011077 has been found to be related to the occurrence of prostate cancer, and SNP rs1966265 influences the therapeutic effect in breast cancer [43,44]. Combined with the current study, these SNPs of FGFR4 may influence a broad spectrum of malignant neoplasm, which needs further investigation.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, both the SNPs revealed the same trend on the UCC, indicating the homogeneous effects of FGFR4 SNPs on the progression and prognosis of UCC. In previous studies, the SNP rs2011077 has been found to be related to the occurrence of prostate cancer, and SNP rs1966265 influences the therapeutic effect in breast cancer [43,44]. Combined with the current study, these SNPs of FGFR4 may influence a broad spectrum of malignant neoplasm, which needs further investigation.…”
Section: Discussionsupporting
confidence: 58%
“…Conversely, an FGFR1-associated SNP (rs17182023) has been linked to a low FGFR1 protein expression and a reduced breast cancer risk [ 65 ]. Certain genetic variants, such as FGFR4 rs1966265 and FGFR2 rs2981578, have also been involved in the outcome of breast cancer patients treated with chemotherapeutic agents [ 66 ]. Overall, the aforementioned findings are not strong enough to suggest that these SNPs may be considered as a therapeutic target in breast cancer patients.…”
Section: Fgfr Genetic Alterations In Breast Cancermentioning
confidence: 99%
“…FGFR4 rs1966265 changes chemotherapy response in breast cancer [ 62 ], higher risk of oral squamous cell carcinoma susceptibility [ 31 ], initiation of cervical cancer (Taiwanese women) [ 19 ], and higher risk of breast cancer in Chinese women of Heilongjiang province [ 16 ]. FGFR4 rs2011077 TC+CC polymorphism is associated with higher tumor stage, tumor size, and grading in urothelial cell carcinoma [ 21 ].…”
Section: Discussionmentioning
confidence: 99%